2018
DOI: 10.1002/vms3.129
|View full text |Cite
|
Sign up to set email alerts
|

First genomic detection of Peaton virus in a calf with hydranencephaly in Israel

Abstract: Simbu serogroup are arbo‐ viruses which are mainly transmitted by Culicoides . Two members of the Simbu serogroup, Akabane and Shuni viruses, have been isolated from congenitally malformed ruminants in Israel. A recent serosurvey revealed that Israeli ruminants have been exposed to several additional Simbu viruses, including Shamonda and Sathuperi that seems to be circulating in Israel. In April 2017, an apparently healthy one‐month‐old male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 14 publications
5
24
0
Order By: Relevance
“…Our phylogenetic analysis, performed on representative sequences of L segments (~200 bp), showed that the virus sequences detected in positive pools from C. imicola , C. oxystoma and C. puncticollis were virtually identical to those of SATV, SHUV and PEAV (Figure b). Moreover, SHUV and PAEV sequences obtained from infected midges were identical to previously published sequences obtained from clinical cases occurring in Israel in 2014 and 2017, respectively (Behar et al, ; Golander et al, ).…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…Our phylogenetic analysis, performed on representative sequences of L segments (~200 bp), showed that the virus sequences detected in positive pools from C. imicola , C. oxystoma and C. puncticollis were virtually identical to those of SATV, SHUV and PEAV (Figure b). Moreover, SHUV and PAEV sequences obtained from infected midges were identical to previously published sequences obtained from clinical cases occurring in Israel in 2014 and 2017, respectively (Behar et al, ; Golander et al, ).…”
Section: Resultssupporting
confidence: 79%
“…Finally, according to our phylogenetic analysis, some of the viral fragments detected from Culicoides pools were identical to the genomic fragments of SHUV and PEAV detected in clinical ruminants during 2014 and 2017, respectively (Behar et al, ; Golender et al, ). Nevertheless, whole‐genome sequencing of viruses isolated from both vectors and ruminants is needed to better understand the transmission of Simbu serogroup viruses by infected Culicoides in Israel.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The most widespread orthobunyavirus is Akabane virus (AKAV), a member of the Simbu serogroup, which is endemic to Africa, Australia, and Asia and causes congenital malformations in ruminants [3]. Other veterinary pathogens of this serogroup include Aino virus, Shamonda virus, and Peaton virus [4,5]. Apart from veterinary pathogens, the genus Orthobunyavirus, also comprises human pathogens, such as Oropouche virus (OROV), which causes a mild, self-limiting febrile illness [6,7].…”
Section: Introductionmentioning
confidence: 99%